MicroRNA controls of cellular senescence - Suh, Nayoung (BMB Rep, 2018)
Cellular senescence is a state of permanent cell-cycle arrest triggered by different internal and external stimuli. This phenomenon is considered to be both beneficial and detrimental depending on the cell types and biological contexts. During normal embryonic development and after tissue injury, cellular senescence is critical for tissue remodeling. In addition, this process is useful for arresting growth of tumor cells, particularly during early onset of tumorigenesis. However, accumulation of senescent cells decreases tissue regenerative capabilities and induces inflammation, which is responsible for cancer and organismal aging. Therefore cellular senescence has to be tightly regulated, and dysregulation might lead to the aging and human diseases. Among many regulators of cellular senescence, in this review, I will focus on microRNAs, small non-coding RNAs playing critical roles in diverse biological events including cellular senescence.